Livestock development in the Caribbean - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The proceedings of the two seminars held in Antigua in November 1990 have now been published. The seminars on Cowdriosis and dermatophilosis of livestock in the Caribbean and Livestock feeding systems for the Caribbean using non-conventional feed...